The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12872-018-0787-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of urinary sodium excretion with blood pressure and risk factors associated with hypertension among Cameroonian pygmies and bantus: a cross-sectional study

Abstract: BackgroundHigh salt intake increases blood pressure (BP) and hypertension risk. This study aimed to examine association of urinary sodium excretion with BP and hypertension correlates among Cameroonian pygmies under hunter-gatherer subsistence mode and Bantus, living in urban area under unhealthy behavioral habits.MethodsIn this cross-sectional cluster sampling study, we randomly enrolled rural pygmies living in Lolodorf and urban Bantus living in Douala. The World Health Organization steps questionnaire was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…Salt intake was found as a key factor of hypertension in previous studies [37]. However, in the current study, the association was only found in women, but not in men.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Salt intake was found as a key factor of hypertension in previous studies [37]. However, in the current study, the association was only found in women, but not in men.…”
Section: Discussioncontrasting
confidence: 71%
“…In a previous study in Vietnam, salt consumption was not significantly associated with high BP at the national level, but the association differed between urban and rural areas in Vietnam [61]. However, the evidence of this association was consistently found in other countries, namely in Brazil [62], China [63], in Cameroon [37]. Moreover, the long term effect of reduction in salt intake on population BP and CVD was summarized from several randomized trials [64,65,66].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The 20 studies [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] used objective measure of the hypertension (Supplemental Table 1, http://links. lww.com/HJH/B114).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Nine and eight of the 20 studies included Yaoundé (capital city) and Douala (main economic city) of Cameroon, respectively. The study quality scores ranged from 8 [45] to 18 [57].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%